Photoaging Photography: Mothers' Attitudes Toward Adopting Skin-Protective Measures Pre- and Post-Viewing Photoaged Images of Their and Their Child's Facial Sun Damage. (October 2016) - Welch, Matthew; Chang, Paul; Taylor, Myra F.
One of the major sources for children to gain knowledge of skin-protective measures is from their parents. Therefore, an imperative exists for parents to model and reinforce the sun-safety practices they want their children to adopt. Although Australian mothers have been the recipients of two extensive sun-safety public health campaigns, little is known about their attitudes, behaviors, and application of health promotion knowledge toward their and their child's ultraviolet (UV) sun exposure. Ten mothers with children aged 4 to 12 years were asked a series of questions about their sun-safety practices, both pre- and post-viewing an UV photoaged photograph of their and their child's face. Interpretive Phenomenological Analysis identified four themes and 12 subthemes. The findings reveal that mothers expressed divergent views on skin protection pre- and post-inspecting their and their child's photoaged photographs. At one end of the viewing spectrum, mothers expressed an opinion that some degree of skin damage was an inevitable reality in Australia's sunny climate, and on the other end of the viewing spectrum mothers expressed their desire to keep themselves and their child out of the sun. Mothers in the mid-range of the spectrum stated that their parenting task was one of transferring the responsibility for adopting skin-protective measures from themselves to their preteen children. The combination of mothers viewing their own photos as well as their child's photograph serves to enhance the difference seen in photoaging damage, which in turn provides greater impetus for mothers to be concerned about photoaging in general.